Unambiguous Acquisition for Galileo E1 OS Signal Based on Delay-And-Multiply - Deng Zhongliang; Xi Yue; Jiao Jichao; Yin Lu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
Galileo E1 Open Service (OS) signal is transmitted with the modulation of Composite Binary Offset Carrier (CBOC). CBOC has a main drawback that is the autocorrelation function has multiple side-peaks, which will lead to ambiguous acquisition. The high rate of data bit and secondary code makes it very difficult to increase coherent integration time. This paper will propose a new scheme based on the delay-and-multiply concept. And also this scheme combines the data channel and pilot channel. Finally, the theoretical results will be given to prove that the new scheme will accomplish unambiguous acquisition and also eliminate the influence of bit transition.